Impacto del sistema general de preferencias sobre los productos agroindustriales y pesqueros exportados por el Perú a Japón (1996-2005) - Tomida Pérez, Mitsuko (2008)
This paper studies how Peru was benefi ted from Japan’s Generalized System of Preferences (GSP) between 1996 and 2005. For this purpose, we are including an econometric model which proves the effects of Japan’s GDP, the variation in the wholesale price index in Peru, the GSP ratio and the trade indicator on non-traditional exports between both countries. This research is mainly focused on analyzing the behavior of agro-industrial and fi shery products benefi ted from the GSP, through statistic charts displaying the trends in non-traditional trade. A survey was conducted among to the sixty largest exporters to Japan to determine the awareness and spreading of this tariff benefi t system among Peruvian exporters of non-traditional products. To enhance this paper, we provide a matrix of potentials with a classifi cation of Peruvian products exported to Japan in order to identify those that Peru might export according to demand.